EFEK PENAMBAHAN BUBUK DAUN KENIKIR (COSMOS CAUDATUS KUNTH) TERHADAP KADAR PROTEIN MINUMAN FUNGSIONAL BERBASIS SUSU KAMBING BUBUK - Candra Saka Nusantari; Annisaa Siti Zulaicha (Analit : Analytical and Environmental Chemistry, 2024)
One variation of functional beverages that is beneficial for the body is powdered goat milk with the addition of kenikir leaf powder (Cosmos caudatus Kunth). Kenikir leaves not only contain bioactive compounds that act as antioxidants, anti-inflammatory agents, and antimicrobials, but they also have high levels of protein, phenolic compounds, carbohydrates, vitamins, and minerals. Therefore, kenikir leaves are utilized as a component to enhance the protein content in functional beverages. The effect of adding kenikir leaf powder to functional beverages on protein content was assessed using the Kjeldahl method, with sample formulations labeled MF(F0), MF(F1), and MF(F2). The results from the Kjeldahl method showed that the highest protein content was found in the MF(F2) sample at 3.58%, while the MF(F1) sample had a protein content of 3.07%, and the MF(F0) sample had 2.49%. This demonstrates that the addition of kenikir leaves increases the protein content in functional beverages. Keywords: kenikir leaves, functional beverages, protein, goat milk.